Penobscot materials, Frank Siebert Papers - Alger, Abby Langdon; Aubéry, Joseph, 1673-1755; Aubin, George F.; Dana, Carol; Dana, Susie; Day, Gordon M.; Goddard, Ives, 1941-; Laurent, Joseph; Neptune, Arthur; Rasles, Sebastien, 1657-1724; Seeber, Pauleena MacDougall; Snow, Dean R., 1940-; et al. (1669)
The Penobscot materials in the Frank Siebert Papers are concentrated in Series III. Siebert collected census material, treaties and treaty minutes, placenames, with a strong representation of songs, stories, and linguistic materials. There are detailed notes about Indian claims in Maine and genealogical information. There are also educational materials for the teaching of the Penobscot language as well as a wealth of information on Penobscot linguistics. Series V, Siebert's notebooks, have extensive grammatical, phonetic, and vocabulary of the Penobscot language. Both Series III and V reflect Siebert's deep interest in the history of Maine and the Eastern Abenaki including archaeological, pre-history, and colonial era documents such as the Eliot Bible, which Siebert owned a rare copy in his library, which was sold at auction. Series VI and VII contain various drafts of essays on Penobscot culture, language, and history. Series XII contains approximately 3 hours of Penobscot language recordings, primarily from the 1930s and 1950s.